2003
DOI: 10.1248/yakushi.123.369
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Distribution of mRNA Expression of Human Cytochrome P450 Isoforms Assessedby High-Sensitivity Real-Time Reverse Transcription PCR

Abstract: Pairs of forward and reverse primers and TaqMan probes specic to each human cytochrome P450 isoform were prepared. Analysis of the mRNA level of each CYP isoform in total RNA from pooled specimens of various human or gans was performed by realtime reverse transcription PCR using an ABI PRISM 7700 sequence detector system. The ex pression of CYP3A4 mRNA was similar to that of CYP3A7 mRNA in the fetal liver, and CYP3A4 mRNA levels in the fetal liver were about 0.1 times lower than in the adult liver. CYP2E1 show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
190
3
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(211 citation statements)
references
References 14 publications
16
190
3
2
Order By: Relevance
“…[55][56][57][58] CYP2C19, CYP2D6 and CYP3A4 are predominantly expressed in human liver. 59) On the other hand, there are species differences between monkeys and humans in the expression of CYP1A1. CYP1A1 is rarely expressed in the human liver, but CYP1A2 is constitutively expressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[55][56][57][58] CYP2C19, CYP2D6 and CYP3A4 are predominantly expressed in human liver. 59) On the other hand, there are species differences between monkeys and humans in the expression of CYP1A1. CYP1A1 is rarely expressed in the human liver, but CYP1A2 is constitutively expressed.…”
Section: Discussionmentioning
confidence: 99%
“…60) Furthermore, the expression level of CYP1A1 mRNA was much lower than that of CYP1A2 mRNA in the human liver. 59) However, the most of CYP1A enzyme expressed in cynomolgus monkey liver is CYP1A1. 61) CYP1A1 mRNA was constitutively expressed (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the predominant -hydroxylases in liver and kidney are microsomal P450s 4A11, 4F2, and 4F3B (4). The -hydroxylation of saturated fatty acids is generally associated with P450 4A enzymes in non-human species, and human P450 4A11 catalyzes the -hydroxylation of lauric acid Ͼ palmitic acid Ͼ arachidonic acid (5).…”
mentioning
confidence: 99%
“…The expression of CYP3A5 was reported in prostate and other extrahepatic tissues by a number of researchers using the RT-PCR methodology (Murray et al, 1995;Yamakoshi et al, 1999;Finnstrom et al, 2001;Nishimura et al, 2003). A more recent study reported the CYP3A5 expression in normal prostate cells but not in prostate cancer cells (Leskelä et al, 2007).…”
Section: Resultsmentioning
confidence: 98%